The Returns to Field of Study in Turkish Labor Market: A Pseudo-Panel Approach - ERİŞ DERELİ, BİLGE (My University, 2022)
Abstract: This study employs pseudo-panel fixed-effects approach to estimate the returns to field of study in Turkey. Repeated cross sections of Turkish Labor Force Surveys between 2016-2019 are used. Year of birth and region are used as grouping variables. The results indicate significant earnings differences across field of study when cohort-fixed effects are controlled. Relative to the base field, Education Sciences, there are higher returns to Environmental Sciences & Mathematics & Statistics and Engineering & Manufacturing & Architecture and Health & Welfare. On the other hand, there are lower returns to Social Sciences & Journalism. The earnings differences are insignificant for the fields Art & Humanities & Languages and Business Administration & Law and Agriculture & Veterinary. These findings are important both for an individual’s subject choice at university and education policies targeting to allocate resources more effectively to tertiary education.
Keywords: Returns to field of study; pseudo-panel; Turkey.